POLA DISTRIBUSI DAN KERAPATAN Arenga undulatifolia Becc. (ARECACEAE) DI HUTAN PEGUNUNGAN BAWAH DI KAWASAN TORO TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - Fitriani Dg. Kalla; Ramadanil Ramadanil; Samsurizal M. Suleman (Biocelebes, 2019)
The research entitled: "The distribution pattern and the density of Arenga undulatifolia Becc. (Arecaceae) in the sub-montane forest of Toro Lore Lindu National Park, Central Sulawesi has been conducted from April to June 2017. The study aimed to find out the distribution patterns and density of Arenga undulatifolia Becc. in the studied area. The research was used transect method which was placed by purposive sampling 50 m in length. The results showed that the distribution pattern of Arenga undulatifolia Becc. was clumped. Density of Arenga undulatifolia Becc tree. The highest was found in transect I with a value of 58.34%, density of Arenga undulatifolia Becc. The highest was obtained in transect III with a value of 29.82% and density of Arenga undulatifolia Becc. The highest was obtained in transect VI with the total value of 42.90%.